SOSIALISASI HASIL PERANCANGAN SKEMATIK TAMAN OLAHRAGA PERUMAHAN GREEN SERANG MADANI PRISMA DI KOTA SERANG - Diana, Rahmi Elsa (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Physical activity and sports are fundamental needs for individuals, necessitating the provision of dedicated spaces within public settings. At the neighborhood scale, the most basic infrastructure to support such activities is the presence of a sports park. Within residential environments, a housing park-typically with a minimum area of 250 m²—serves multiple functions, including stormwater management, local microclimate regulation, and facilitation of socio-economic and cultural interactions. This study examines the case of the Green Serang Madani Prisma housing complex, where a badminton court was constructed informally, without reference to established design standards. Recognizing the importance of thoughtful spatial planning, a community service initiative was undertaken in 2020 by the author, encompassing the development of a schematic design for the sports park and the implementation of a public socialization program. The design methodology was structured into three sequential phases: analysis, synthesis, and evaluation. Initial activities included participatory discussions and direct site observations to identify resident behaviors and assess existing physical conditions. The design output emphasized three principal criteria: functional relevance, design innovation, and aesthetic value. Based on evaluative feedback from residents, the schematic design achieved satisfaction ratings of 85.45% for functionality, 74.55% for innovation, and 87.27% for aesthetics. The initiative concluded with a socialization session aimed at disseminating design outcomes and fostering community understanding. According to questionnaire results, the effectiveness of this outreach activity exceeded 75%, indicating a positive reception and enhanced awareness among residents regarding the importance of design-integrated sports facilities in residential contexts. --- Setiap orang butuh bergerak dan berolahraga. Dalam konteks publik, aktivitas berolahraga perlu diwadahi, salah satunya yang paling sederhana dengan menyediakan taman olahraga skala RT. Taman RT adalah taman yang melayani skala RT dengan luasan minimum 250 m2. Taman RT berfungsi sebagai daerah resapan air, pengendali iklim mikro, serta tempat aktivitas ekonomi dan sosial budaya masyarakat. Pada kegiatan pengabdian ini, terdapat pembangunan lapangan bulutangkis yang sedang berlangsung di Perumahan Green Serang Madani Prisma. Pembangunan tersebut memerlukan perhatian khusus terutama dari sisi perancangan. Lapangan bulutangkis dibangun secara insidental tanpa adanya gambar sebagai petunjuk konsep perancangan. Pada tahun 2020 penulis telah melakukan kegiatan pengabdian yang terdiri dari kegiatan perancangan taman olahraga dan kegiatan sosialisasi hasil perancangan. Tahapan perancangan setidaknya terbagi ke dalam tiga tahap yaitu tahap analisis, tahap sintesis dan tahap evaluasi. Tahapan perancangan dimulai dengan kegiatan diskusi dan pengamatan tapak untuk menggali pemahaman terhadap aktivitas warga dan juga kondisi eksisting. Kekhasan karakteristik perancangan merujuk pada tiga hal yaitu penyesuaian rancangan dengan kebutuhan, terdapat inovasi, serta pertimbangan estetika visual. Berdasarkan penilaian evaluasi kegiatan pengabdian, pemenuhan indikator kesesuaian perancangan menurut warga yaitu 85,45% tepat guna, 74,55% untuk indikator inovasi dan 87,27% untuk indikator estetika. Kegiatan perancangan skematik dilanjutkan dengan kegiatan sosialisasi sebagai sebuah bentuk edukasi kepada warga di perumahan tersebut. Menurut kuesioner, tingkat keberhasilan kegiatan sosialisasi lebih tinggi dari 75%.